Trends in Industry Payments to Orthopedic Foot and Ankle Surgeons from 2014 to 2018. Issue 4 (22nd October 2020) - Mody, Kush S.; Liou, Lathan; Joshi, Tej; Mikhail, Christopher; Barbera, Joseph; Selverian, Stephen; Vulcano, Ettore
Category: Other Introduction/Purpose: The establishment of the Open Payments Database (OPD) in 2014 made public all financial payments to physicians and hospitals by pharmaceutical and medical device companies. Since then, numerous studies have analyzed industry payment data to elucidate any correlations and trends. The purpose of this study is to examine trends in industry payments to orthopedic foot and ankle surgeons from 2014 to 2018. Methods: The Open Payments Database (OPD) was queried to collect information regarding industry payments to orthopedic foot and ankle surgeons and all orthopedic surgeons from 2014 to 2018. Information was collected on physician education, regional distribution of physicians paid, number of physicians paid, median payment amount, and payment type. Further analyses were conducted on the median payment amount to the top 5% of earners and the other 95%. Median amounts were analyzed using Mann-Whitney U non-parametric tests. Results: Of the 1, 416 physicians classified as orthopedic foot and ankle surgeons, Doctors of Osteopathy and Medical Doctors received significantly higher payments than Doctors of Podiatric Medicine (597 vs. 35, P=9x10-113). Only osteopathic and allopathic physicians were included in the main analyses. No significant difference was reported from 2014 to 2018 in the median payments to orthopedic foot and ankle surgeons overall ($616 vs. $810; P=0.13), in the top 5% ($148, 864 vs. $158, 349; P=0.53), and other 95% ($542 vs. $730; P=0.10). There was no significant difference in payments related to consulting fees, entertainment, food and beverages, gifts, grants, honoraria, royalty and licensing fees, speaker and faculty fees, and travel and lodging. There was a significant increase in industry payments related to education ($750 vs. $1370; P=0.002). Conclusion: Following the establishment of the Open Payments Database in 2014, it was expected that industry payments would decrease significantly. However, no change was seen in payments to orthopedic foot and ankle surgeons and there remains a very large distribution in surgeon compensation. In fact, the top 5% of surgeons compensated account for over 99% of the total industry payments. While there are many factors that could account for this, foot and ankle surgeons should use data extracted from the OPD as a guide to ensure fair and equitable compensation for their work in industry.